(untitled) (Journal of the College of Basic Education, 2022)
The researcher used a teaching method (training) to identify its effect on the learners and to provide appropriate learning opportunities through the optimal investment of effort and time. In this method, some offensive skills were learned among middle school students in the second grade (males) in Al-Rabea Intermediate School for Boys.